Experimental investigation on strengthening of infilled frame structures by profiled steel sheet shear walls. Issue 4 (April 2016) - Feng, Ningning; Cao, Pingzhou; Wu, Kai; Zhang, Pengcheng
This article presents an experimental study on seismic performance of three reinforced concrete frames. Three 1/3-scale, one-bay, two-story specimens are constructed and tested in the test. One specimen is bare; another is reinforced by profiled steel sheet shear walls; the third one is filled with infill walls and reinforced by profiled steel sheet shear walls. Experiment investigates some characteristics of three test specimens, such as strength, stiffness, and energy dissipation. Test results show that these characteristics of infilled frame structure have been improved prominently. Comparing with the bare and the second specimen, the strength is enhanced by 307.3% and 109.28%, the stiffness is increased by 103.17% and 12.27%, and cumulative energy is improved by 291.37% and 106.45%, respectively. The results indicate that profiled steel sheet shear walls can cooperate with infill walls effectively and improve seismic performance of reinforced concrete frame structure significantly. The seismic strengthening method, profiled steel sheet shear walls reinforce infilled frame structures, is proved to be efficient.